Plant essential oils, trans-anethole and eugenol, for housefly knockdown and mortality - Sirawut Sittichok; Hataichanok Passara; Jirisuda Sinthusiri; Mayura Soonwera; Thanaset Thongsaiklaing; J. Glenn Morris; Tanapoom Moungthipmalai; Cheepchanok Puwanard; Sumonrat Jintanasirinurak (International Journal of Agricultural Technology, 2025)
The knockdown and mortality of some compounds from natural oils (trans-anethole, eugenol and a combination of trans-anethole and eugenol) against adult houseflies (Musca domestica) compared with cypermethrin was investigated. The knockdown and mortalities were highest at 100% of 1% trans-anethole with KT50= 31 min and LT50 = 31 min. The mortality index of trans-anethole was 82.1 times that of cypermethrin. In contrast, 1% eugenol had knockdown and mortality was 36% and 0.5% trans-anethole + 0.5% eugenol had knockdown and mortality of 68%, with mortality indexes of 1.6 and 3.2 times versus cypermethrin. The trans-anethole high toxicity and low residue made it a superior control for houseflies.
Keywords: Insect Pest Control Strategies; Insect and Pesticide Research; Insect Utilization and Effects